Yield Performance and Stability of Some Indian Castor Hybrids in Nigerian Ecology - OKE, C. O. (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2024)
Castor (Ricinus communis L.) is an industrial oil crop that is widely recognized as an ideal crop for tropical and subtropical regions. Nigeria has been identified as a country with high potential to meet her national castor oil need and provide surplus for export. This potential can be harnessed, only if adequate production technologies, such as improved varieties, are available to the farmers. In this research, three FTB castor hybrids (Code 11, Code 22 & Code 33) and two local checks (NCRICAS1 & NCRICAS1) were assessed for their yield performance and stability in Nigeria. The castor genotypes were evaluated in a replicated plots across six locations in the Southern and Northern Guinea savanna ecologies of Nigeria. The results revealed significant differences for traits assessed among the genotypes. Average seed yield among the hybrids ranged between 596.58kg/ha and 1372.49kg/ha. Average seed yields of the checks ranged between 849.58kg/ha and 1239.63kg/ha. The hybrid Code 33 out yielded the two local checks at four locations (i.e Badeggi, Benue, Kebbi & Sokoto) out of the six locations. The check 1 (Acc.036) recorded significant higher yield (1705.28kg/ha & 1648.15kg/ha) than the hybrid Code 33 (1573.91kg/ha & 867.58kg/ha) at Bacita and Bauchi locations. Besides recording comparable seed yield to the best hybrid (Code 33), the local check 1 (Acc.036) matured earlier than the hybrids evaluated. The GGE biplot view revealed good stability and responsiveness for both hybrid Code 33 (G5) and Acc.036 (G2). Based on performance per se, the hybrid Code 33 showed better adaptation to the ecology. However, further assessment on oil quantity and quality, and cost benefit analysis of the hybrid(s) in comparison to the local varieties is highly recommended.